Prehistoric Trade And Culture Contact Between Bukit Tengkorak And Other Sites In Southeast Asia And The Pacific Region. - Chia, Assoc Prof. Dr. Stephen, Ming Soon (2004)
This paper describes the initial results of my SEASREP research project entitled "Prehistoric trade a d culture contact between Bukit Tengkorak and other sites in Southeast Asia and the Pacific region". It presents the research activities and findings during the first year of the project from 2002-2003 and a brief overview of the background of the research project, the research aims and methodology as well as plans for future research.